Mobile Application Inventory Sarana dan Prasarana Sekolah Dasar - Emerensiana Ngaga; Sisilia D. Bakka Mau; Alfry Aristo J Sinlae (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
This mobile-based facility and infrastructure inventory application are engineered because there is still a conventional data collection process that is recorded in a logbook (a special book for inventory) so that in the logbook the number of items available is not updated in real-time if there are incoming goods, outgoing goods, goods borrowed, goods repaired or damaged goods. This application engineering follows the stages of the Extreme programming system development method, which consists of planning, designing, coding, and testing. The result of this research is a mobile application that can be used to manage inventory data of facilities and infrastructure at SD ABC which is engineered using Android Studio and the Java programming language. The XP method was successfully implemented so that the application was successfully engineered according to the predetermined time estimate. The application was successfully tested using the Usability standard with an average percentage value of 85%, and after being converted it entered the good category, so it can be concluded that the application is feasible to use in facilitating the management of school facilities and infrastructure inventory data.